2013
DOI: 10.3892/br.2013.186
|View full text |Cite
|
Sign up to set email alerts
|

Association of the interleukin-18 −137 C/G, −607 A/C polymorphisms with type 1 diabetes: A meta-analysis

Abstract: Abstract. Published data on the association between interleukin (IL)-18 gene polymorphisms (-137 C/G, -607 A/C) and type 1 diabetes (T1D) risk are inconclusive. To obtain a more precise estimation of the association between the IL-18 gene polymorphisms and T1D, a meta-analysis was performed. A total of 11 studies including 5,945 cases and 6,404 controls were included in the analysis of the association between -137 C/G and T1D risk. No significant association between -137 C/G and T1D risk was observed in the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Fatima et al found that increased IL18 levels in women with GDM were correlated with low-grade inflammation and insulin resistance [26]. IL18 gene polymorphisms have been investigated among patients with type 1 and type 2 diabetes [27][28][29][30][31]. Several studies suggest that these polymorphisms may be associated with an increased risk of diabetes and its cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Fatima et al found that increased IL18 levels in women with GDM were correlated with low-grade inflammation and insulin resistance [26]. IL18 gene polymorphisms have been investigated among patients with type 1 and type 2 diabetes [27][28][29][30][31]. Several studies suggest that these polymorphisms may be associated with an increased risk of diabetes and its cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency in NCC on β cells or IL-18R in acinar cells reduces β cell proliferation and islet size with a concomitant rise in β cell apoptosis and exocrine macrophage accumulation ( 146 ). T1D is possibly a Th1 cell-mediated disease ( 147 ) that affects millions of people around the world and its etiology is complex with a combination of genetic and environmental pathogenic factors ( 148 , 149 ). Although the Human leukocyte antigen (HLA) genes are known to have a role in the development of T1D, evidence have continued to indicate that the pro-inflammatory IL-18 contributes to the genetic susceptibility to T1D ( 150 ).…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…As shown in Table 2, the product type did not moderate the effect of product touch on consumer attitude (QB ${Q}_{B}$ = 0.482, p = 0.487). However, past research suggested that researchers could still compare the effect sizes between conditions when the difference between groups was insignificant (Li, 2013; Maity et al, 2014). Further group‐wise comparisons showed that, for utilitarian products, the effect size between product touch and consumer attitude was positive and significant (ρ $\rho $ = 0.259, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%